P1.16 Acquisition of azithromycin resistance in neisseria gonorrhoeae via intragenus recombination. (8th July 2017) - Wadsworth, Crista; Grad, Yonatan
Abstract : Introduction: Reduced susceptibility to azithromycin (Azi RS ) is increasing in frequency in Neisseria gonorrhoeae . We have shown that non-gonococcal alleles at the mtr operon, encoding the MtrCDE efflux pump and the transcription repressor, are associated with Azi RS and sought to define further their role in resistance. Methods: We transformed a susceptible strain (MIC <0.125 µg/mL) using gDNA from gonococcal donors carrying mosaic mtr loci and selected for Azi RS (MIC ≥2 µg/mL) transformants. We sequenced the transformants' genomes to define the transformed DNA, compared growth rates of parent and transformant strains, described the phylogenetic distribution of mtrR, mtrC, mtrD, and mtrE alleles across Neisserial species, and defined the sequence diversity and π at these loci. Results: Transformation studies confirm mosaic mtr alleles cause Azi RS . Phylogenetic patterns support frequent Azi RS -associated recombination of mtrR, mtrC, and mtrD between N. gonorrhoeae and other Neisseria. Conversely, 16 S and mtrE displayed almost exclusive species-based clade topology and no recombination events associated with Azi RS . Within gonococcal populations, reduced nucleotide diversity at mtrE (n=1102, π=0.0054) compared to mtrRCD (π=0.014) suggests either equal rates of interspecific recombination across the mtr operon with increased levels of purifying selection acting to purge the introduction of novel alleles at mtrE, or a 'hotspot' of interspecific recombination at mtrRCD . Recombination of mosaic mtr alleles into novel gonococcal genomic backgrounds does not deleteriously affect growth rate in vitro, raising questions regarding the associated fitness cost. Conclusion: This work supports that Neisseria serve as a reservoir of gonococcal Azi RS through interchange of mtr alleles. The genomic epidemiological evidence of multiple acquisitions of these alleles underscores the importance of screening for mtr mosaics to prevent outbreaks of Azi RS .